Dividend Yield, Earning Volatility, And Leverage Effect On Volatility Stock Prices Of Consumption Goods Companies 2018-2022 - Verlyn Winata; Agustin Ekadjaja (Studi Ilmu Manajemen dan Organisasi, 2025)
Abstract:Purpose: This study aims to analyze the impact of dividend yield, earnings volatility, and leverage on stock price volatility in consumer goods companies from 2018-2022 and test the relevance of existing theories in the Indonesian context.Research methodology: This study is a quantitative study, examining the causal relationship of independent variables such as dividend yield, earning volatility and leverage to the dependent variable, namely stock price volatility. Data were collected by looking at the financial statements of each company and the stock prices of companies engaged in the consumer goods industry listed on the Indonesian Stock Exchange for the period 2018-2022. The collected data were then processed using the SPSS program.Results: Dividend yield and earning volatility variables have a negative but insignificant effect on stock price volatility in consumer goods industry companies. While the leverage variable has a significant and positive effect on stock price volatility in consumer goods industry companies.Conslusions: This study found that dividend yield and earnings volatility do not significantly affect stock price volatility, while leverage has a significant impact. The study is limited to the period of 2018-2022 and consumer goods companies listed on the IDX.Limitations: The independent variables used in the study that explain stock price volatility are only limited to three variables, namely dividend yield, earning volatility and leverage. There are limitations to the research period used in the study, namely 2018-2022 so that the study is only able to explain conditions in that period, and the limited research sample used, namely around companies engaged in the consumer goods sector listed on the Indonesia Stock Exchange (IDX)Contribution: This study contributes to the existing literature by providing insights to new investors regarding stock information that influences investment decisions. This study highlights that stock price volatility that occurs can be influenced by many factors and can be additional information in an investor's investment decision.Keywords: Dividend Yield, Earning Volatility, Leverage, Stock Price VolatilityHow to Cite: Winata, V, F., Ekadjaja, A. (2025). Dividend Yield, Earning Volatility, And Leverage Effect On Volatility Stock Prices Of Consumption Goods Companies 2018-2022. Studi Manajemen dan Ilmu Organisasi, 6(1), 53-61.